KONDISI EKOSISTEM PADANG LAMUN DI PERAIRAN PANTAI GUNUANG CINDAKIR DAN PANTAI NIRWANA KOTA PADANG PROVINSI SUMATERA BARAT - Mustafa, Amila; Amrullah, Mohd. Yusuf; Syafrialdi, Syafrialdi (Universitas Muara Bungo, 2023)
The seagrass ecosystem is one the important ecosystems that can support the life of various living things. The research was conducted on a tourist beach in The city of Padang, namely, Gunuang Cindakir Beach and Nirwana Beach, which has seagrass ecosystems located in tourist beach locations, data or studies on ecosystem conditions are needed for seagrass beds which are beach tourism locations. The research method is in taking the sample was carried out using the quadratic transect method and data collection based on the purposive sampling method. The results showed that at the research location, only one species of seagrass was found, namely Thalassia hempricht. And the value of the percentage of covered Seagrass obtained at Gunuang Cindakir Beach was 26,95% and at Nirwana Beach by 41,44%. At both research locations are in the low category with poor and less rich seagrass conditions.